Examining the relationship between food insecurity and students’ academic performance in public universities / Nur Farrah Yasmin Abdul Latib ... [et al.] - Abdul Latib, Nur Farrah Yasmin; Jalis, Mohd Hairi; Md Rus, Mohammad Hafizi; Che Deraman, Nor Saadah (2021)
This study examines the relationship between food insecurity and academic performances among university students in Selangor, Malaysia. Food insecurity exists whenever people have limited food access at all times for an active and healthy life. In the case of Malaysians, their multicultural identity has expanded their palate and surrounded them with various food choices in their daily life. However, only a few are well-informed of the story behind food production and its quality. Limited knowledge and understanding of health, particularly daily dietary food intake, might slowly make people descend to food insecurity. Therefore, it is essential to understand the consequences of this issue. A total of 400 survey data using a self-administrated questionnaire were collected among students across public universities in Selangor, Malaysia. Statistical analysis revealed that food quality significantly influences students’ academic performances. Students at a lower risk of food insecurity included those who reported living with their parents and those who received monthly allowances from government agencies and their parents. In addition, food-secure students were more likely than food-insecure students to report a higher GPA versus a lower GPA. These findings compel relevant authorities, including university and food-related service providers, to consider the importance of food quality and students' amount of food intake as these factors significantly influence their academic performances. Therefore, this study suggests further investigation with a combination of various study settings and scope probably could gain a deeper understanding of and refine the existing theory of human belief towards food consumption.